MASALAH-MASALAH SOSIAL BUDAYA DALAM PEMBANGUNAN KESEHATAN DI INDONESIA - Rusmin Tumanggor (Jurnal Masyarakat dan Budaya, 2010)
Health is one of basic needs of human being. The health program effort are including constructive, preventive, curative, rehabilitative, and preservative. Objects of program ranging from individuals, households, families, communities, nations to the world community. Region spatially, starting from the village, subdistrict, district, provincial, national, and international. Institutions ranging from neighborhood health center services, public health offices, health centers, and government-run hospitals and the community. Health implementation efforts have strengths, weaknesses, opportunities and challenges. The multidimentional components contribute to health status of society. Socio-cultural factors could also be considered as one of determinant factors of health status. Keywords: health, health seeking effort, socio-cultural.